Double valuted tomb in Sv. Luke's Bay near Jelsa (In situ, 2024)
In the area of the Sv. Luke's Bay, which is also called "Carkvica" or "Crikvica", in November 2023 in cooperation of the Department of Archeology University of Zadar and archaeological company Kantharos d.o.o., field survey and trial archaeological excavations were carried out. On the eastern part of the bay, not far from the smaller medieval Church of St. Luka, there are remains of ancient architecture, probably a rustic villa and under the sea remains of a dock, while a double vaulted tomb is located on the opposite, western shore of the bay. Research included cleaning and documenting of the double vaulted tomb. It turned out that it is a late antique tomb and that it was most likely built near early Christian church.
Keywords: Hvar; Sv. Luka; double vaulted tomb; villa rustica; dock